1999
DOI: 10.1097/00005176-199903000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Oxide Sedation in Pediatric Patients Undergoing Gastrointestinal Endoscopy

Abstract: Entonox provides rapid and effective analgesia without heavy sedation, leads to adequate relaxation and cooperation, and facilitates quick and efficient endoscopy. The effect of Entonox was of short duration, allowing the children to leave the endoscopy unit without need for a long recovery period. The adverse effects of Entonox appeared to be minor, and their duration was always brief. Nitrous oxide-oxygen inhalation may provide a valuable alternative to conventional sedation regimens during gastrointestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…1,5,11 Although the favorable effects of nitrous have been lauded for over 150 years, Griffin's landmark 1983 study of over 3,000 procedures first outlined the technique for children treated as outpatients. 12 In this report, we show its usefulness in a novel setting, for inpatients and outpatients on a pediatric surgical service.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,11 Although the favorable effects of nitrous have been lauded for over 150 years, Griffin's landmark 1983 study of over 3,000 procedures first outlined the technique for children treated as outpatients. 12 In this report, we show its usefulness in a novel setting, for inpatients and outpatients on a pediatric surgical service.…”
Section: Discussionmentioning
confidence: 99%
“…Michaud et al, evaluated the efficacy of entonox for the induction of analgesia during endoscopy in pediatric and reported that prescription of entonox led to better cooperation in patients and its short duration of action decreased the recovery time in the patients, and had little side effects (17). results regarding the use of inhaled entonox during intraarticular injections in children with juvenile idiopathic arthritis (18).…”
Section: Discussionmentioning
confidence: 99%
“…Michaud and Gottrand[13] showed that the time taken to regain consciousness was short following nitrous oxide sedation, which could effectively meet the sedative requirements for children undergoing gastroscopic examination, thus providing a valuable alternative method of sedation. Michaud et al[14] compared the sedative effects of propofol and nitrous oxide in patients undergoing colonoscopy, and showed that both agents had similar sedative and pain-relieving effects, facilitated the operation, and shortened recovery time. In addition, nitrous oxide has demonstrated minimal effects on nerve function and therefore does not affect the patient’s ability to drive[15].…”
Section: Discussionmentioning
confidence: 99%